Raising Spanish Children With an Antisocial Tendency: Do We Know What the Optimal Parenting Style Is? - Garcia, Oscar F. (Journal of interpersonal violence, 2021)
Families can play an essential role in preventing violent and antisocial behaviors, which are considered a significant public health issue. However, some studies argue that most children are antisocial only during adolescence, and even teenagers can mimic antisocial behavior in ways that are normative and well-adjusted. This study analyzed patterns of competence and adjustment in young adults with and without an antisocial tendency during adolescence from authoritative (characterized by warmth and strictness), authoritarian (strictness but not warmth), indulgent (warmth but not strictness), and neglectful (neither warmth nor strictness) families. Emergent research has indicated that in a European context, the indulgent parenting style is optimal. Offspring’s competence and adjustment were captured through self-esteem (academic and family), psychosocial development (self-competence and empathy), and low emotional maladjustment (nervousness and hostility). Participants consisted of a community sample of 489 Spanish young adults, 191 men (39.1%) and 298 women (60.9%), aged 18 to 34 years old. The design was a 4 × 2 × 2 × 2 MANOVA (parenting style × antisocial tendency × sex × age). Analysis of main effects showed that youths with an antisocial tendency have less self-esteem and psychosocial development, but more emotional maladjustment. Regardless of the parenting style, an antisocial tendency during adolescence is consistently associated with worse adjustment in young adults. Both the authoritative and indulgent parenting styles are consistently associated with better outcomes (higher self-esteem and psychosocial development, and lower emotional maladjustment) than the authoritarian and neglectful parenting styles. However, there are interactions between the parenting style and the antisocial tendency. For young adults without an antisocial tendency, only indulgent parenting is associated with less emotional maladjustment. These results support the idea that in Europe the indulgent parenting style performs better than the authoritative style, but only when raising adolescents without an antisocial tendency. For young adults with an antisocial tendency, indulgent and authoritative parenting are equally optimal for all the studied outcomes.